Feedback in language learning and teaching - Komorowska, Hanna (Glottodidactica, 2018)
The text analyzes routes and ways of processing feedback as well as discusses the most important psychological, pedagogical and linguistic factors influencing the effectiveness of feedback in developing learner autonomy and determining its impact on cognitive and affective processes in the learner. It also sets out to assess the place of feedback in the evaluation of educational attainment and to identify ways of promoting so-called formative feedback, both on the school-level and in the language classroom. Implications for developing teacher autonomy via pre- and in-service teacher education are also sought